Enucleation for low-grade branch duct intraductal papillary mucinous neoplasms: long-term follow-up - Kaiser, Jörg; Alhalabi, Karam T.; Hinz, Ulf; Mayer, Philipp; Tjaden, Christin; Büchler, Markus W.; Hackert, Thilo; Loos, Martin (Surgery, 2022)
Background - Pancreatic enucleation allows resection of branch-duct intraductal papillary mucinous neoplasms with full parenchyma preservation. The aim of this study was to assess intraductal papillary mucinous neoplasms recurrence and functional outcomes during long-term follow-up after enucleation. - Methods - Patient characteristics, as well as radiologic and clinicopathologic follow-up data of patients who underwent enucleation for branch-duct intraductal papillary mucinous neoplasms between 2004 and 2014, were analyzed. Quality of life was assessed using the EORTC QLQ-C30 and QLQ-PAN26 questionnaires. - Results - Seventy-four patients underwent enucleation for low-grade branch-duct intraductal papillary mucinous neoplasms in 71 and high-grade branch-duct intraductal papillary mucinous neoplasms in 3 patients. Long-term follow-up data were available for 66 patients (89%; median follow-up: 87 months). Radiologic imaging (n = 56) showed intraductal papillary mucinous neoplasm recurrence in 10 patients (18%) including local recurrence at the site of enucleation in 3 patients (5%) and new onset intraductal papillary mucinous neoplasms manifestation in 7 patients (13%) at a distant site in the pancreatic remnant. Four patients (6%) underwent reoperation. Two of these patients had intraductal papillary mucinous neoplasm-associated carcinoma, one of them at the enucleation site. During the follow-up period, no intraductal papillary mucinous neoplasm-related deaths occurred and no new onsets of insulin-dependent diabetes mellitus were observed. QLQ-C30 revealed a global health status of 66.0% and overall functioning and symptom scores of 81.0% and 22.8%, respectively. Additionally, QLQ-PAN26 showed an overall symptom score of 26.5%. - Conclusion - Enucleation is an organ-preserving surgical treatment option for low-grade branch-duct intraductal papillary mucinous neoplasms with low local recurrence risk and excellent functional long-term outcome. However, postoperative life-long follow-up must be performed as for any type of partial pancreatectomy for intraductal papillary mucinous neoplasms due to the risk of recurrence and potential malignancy.